A noção de integral do contexto das concepções operacional e estrutural - Oliveira, Aguinaldo Herculuno de (2004)
The research analyses the notion of integral in two Calculus textbooks. The works takes as its theoretical basis the theory of Sfard, according to which mathematical notions are treated initially as processes evidencing their characteristics (operational conception) and then as objects (structural conception). The passage from the first to the second involves three hierarchical stages: interiorisation, condensation and reification. The books chosen for analysis were Calculus by M. Spivak and Cálculo by J. Stewart. The first book presents integral axiomatically, that is, starting from a refined construction of definitions and theorems. It firstly defines integral and goes on to consider its properties. The second presents integral from the basis of a long introduction to the calculation of areas, after which integral is defined and its properties obtained. Its strong point is the enormous quantity of exercises involving algorithmic manipulations and applications. The research shows that the formal treatment of Spivak goes against the theory of Sfard, in which she argues that an operational conception of a notion she precedes a structurally conception. Nonetheless, in spite of this, there are situations in which this order is respected. Various exercises with structural characteristics are included in the book which might favour the passage between the two conceptions. In Stewart, the treatment of integral respects the hierarchical ordering of conceptions postulated by Sfard, however the book includes few exercises with structural characteristics, although the chapters which treat the notion do present projects which could provide opportunities for its reification